Oxidation of GaSb(100) and its control studied by scanning tunneling microscopy and spectroscopy - J. Mäkelä; M. Tuominen; M. Yasir; M. Kuzmin; J. Dahl; M. P. J. Punkkinen; P. Laukkanen; K. Kokko; R. M. Wallace (AIP Publishing, 2022)
Atomic-scale knowledge and control of oxidation of GaSb(100), which is a potential interface for energy-efficient transistors, are still incomplete, largely due to an amorphous structure of GaSb(100) oxides. We elucidate these issues with scanning-tunneling microscopy and spectroscopy. The unveiled oxidation-induced building blocks cause defect states above Fermi level around the conduction-band edge. By interconnecting the results to previous photoemission findings, we suggest that the oxidation starts with substituting second-layer Sb sites by oxygen. Adding small amount of indium on GaSb(100), resulting in a (4 × 2)-In reconstruction, before oxidation produces a previously unreported, crystalline oxidized layer of (1 × 3)-O free of gap states.